Imaging manifestations of hereditary hemorrhagic telangiectasia with pulmonary arterial hypertension: a case report - Qin, Guangmei; Chen, Siqi; Huang, Fuling; Mo, Liupei; Li, Kai (Frontiers in Cardiovascular Medicine, 2025)
Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal dominant disorder. Pulmonary arterial hypertension (PAH) is an uncommon complication (affecting <1% of HHT patients). Here, we report the clinical and imaging findings of a rare case of HHT complicated by PAH in a 41-year-old woman. The patient experienced recurrent exertional dyspnea for over 1 year, accompanied by chest tightness and pain, coughing, and production of white mucus. Her medical history included recurrent epistaxis and bilateral lower extremity edema. Due to persistent symptoms, she was hospitalized for further evaluation. Imaging revealed multiple dilated, tortuous vessels and arteriovenous fistulas in both lower lung lobes and the liver. Additionally, myocardial edema and fibrosis were observed in the ventricular insertion points, interventricular septum, right ventricular inferior wall and left ventricular free wall. Reduced pulmonary artery peak flow velocity, maximal flow, and mean wall shear stress (mWSS) were noted. Right heart catheterization confirmed pre-capillary PAH, and genetic testing identified an ACVRL1 mutation. Symptomatic supportive care was provided during hospitalization. We discussed the relationship between PAH and HHT as well as the characteristics of both conditions.